The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/cells11233814
|View full text |Cite
|
Sign up to set email alerts
|

Manganese Deficiency Suppresses Growth and Photosynthetic Processes but Causes an Increase in the Expression of Photosynthetic Genes in Scots Pine Seedlings

Abstract: Manganese deficiency is a serious plant nutritional disorder, resulting in the loss of crop productivity in many parts of the world. Despite the progress made in the study of angiosperms, the demand for Mn in gymnosperms and the physiological responses to Mn deficiency remain unexplored. We studied the influence of Mn deficiency for 24 weeks on Pinus sylvestris L. seedling growth, ion homeostasis, pigment contents, lipid peroxidation, chlorophyll fluorescence indices and the transcript levels of photosynthetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…This probably resulted from the negative effect of Mn deficiency on water photolysis and the impaired function of the electron transport chain on the chlorophyll thylakoid membranes from PSII to PSΙ [ 32 , 33 ]. We also found that the tolerant genotype mitigates damage to the photosynthetic machinery by dissipating excess light energy in the form of heat, whereas the sensitive genotype photochemical energy conversion and protective regulatory mechanisms cannot completely process the absorbed light energy; this leads to increasingly severe photodamage in maize seedlings, which was also reported in previous studies [ 2 , 12 , 34 , 35 ]. Moreover, we observed that the young leaves of sensitive genotype maize seedlings showed striped chlorosis when they were slightly manganese deficient, and the leaf area decreased significantly, especially when they were completely manganese-deficient.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…This probably resulted from the negative effect of Mn deficiency on water photolysis and the impaired function of the electron transport chain on the chlorophyll thylakoid membranes from PSII to PSΙ [ 32 , 33 ]. We also found that the tolerant genotype mitigates damage to the photosynthetic machinery by dissipating excess light energy in the form of heat, whereas the sensitive genotype photochemical energy conversion and protective regulatory mechanisms cannot completely process the absorbed light energy; this leads to increasingly severe photodamage in maize seedlings, which was also reported in previous studies [ 2 , 12 , 34 , 35 ]. Moreover, we observed that the young leaves of sensitive genotype maize seedlings showed striped chlorosis when they were slightly manganese deficient, and the leaf area decreased significantly, especially when they were completely manganese-deficient.…”
Section: Discussionsupporting
confidence: 84%
“…Manganese (Mn) is an essential micronutrient for the normal growth and development of higher plants [ 1 ]. As an important component of the oxygen evolution complex (OEC) of Photosystem II (PSII) [ 2 , 3 ], it strongly influences photosynthetic water oxidation processes [ 4 ], carbohydrate metabolism [ 5 ], and nitrate assimilation in plants [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Notable diminishments of these growth parameters were also observed in many plant species when lacking Mn, B, Zn, and Cu, such as cabbage [45], tobacco [46], and lettuce [47]. However, for these mentioned micronutrient deficiencies, we found that only slight nutrient deficiency symptoms were developed in leaves (Figure 2) due to the fact that the visual symptoms only appeared when the plant growth was severely depressed [42,48]. These four micronutrients were strongly related to photosynthesis.…”
Section: Basil Growth and Photosynthetic Ability As Affected By Nutri...mentioning
confidence: 52%
“…These three micronutrients take part directly and/or indirectly in plant nutrition while their deficiency may cause growth retardation in plants, and finally plant death (Robe et al 2021;Ivanov et al 2022;Ahmadi et al 2023;El Amine et al 2023;Younas et al 2023). On the other hand, they become rapidly immobile in soils within short time periods of application (Abbas and Salem 2011;Abbas 2013;Elshony et al 2019).…”
Section: Introductionmentioning
confidence: 99%